Correlation Analysis Between Production Level, National Income, Investment, Unemployment and Poverty in Indonesia - Sessu, Andi (International Journal of Psychosocial Rehabilitation, 2020)
Economy development in Indonesia is quite prospective, especially on four variables of both macro and micro economy, such as production level, national income, investment since 2004 until 2018 can be categorized experiencing rapid growth and the level of unemployment and poverty is getting lower.However, collectively, coefficient correlation r = 0,961 demonstrates that the influence of rice, corn and soybeans production level are very strong on national income level and coefficient determination R2 = 0,924 or 92,4 % demonstrates that the amount of contribution of influence on rice, corn, and soybeans production level collectively in 92,4% upon national income level, while it gives negative influence on unemployment level which means that more increase in national income level 2,765, it makes lower unemployment level, while investment level is still give positive influence on unemployment level which means unable to influence the level of decrease upon unemployment, however, collectively, the value of coefficient correlation r = 0,940 demonstrate that the influence of national income and investment level are collectively very strong and coefficient determination is R2 = 8,884 or 88,4 % which means the contribution of influence on national income and investment level are collectively in 88,4% and level of unemployment gives positive influence on poverty level that means more increase in unemployment also more increase in poverty that is if unemployment increase one score, poverty is also increase in 2,717 on Constanta 83266, while coefficient correlation r = 0,949 meaning the influence of unemployment level is very strong on poverty and determination in R2 = 0,901 or 90,1 % demonstrate that the amount of contribution of the influence on unemployment level in 90,1%.